Abscisic Acid: A Novel Nutraceutical for Glycemic Control - Zocchi, Elena; Hontecillas, Raquel; Leber, Andrew; Einerhand, Alexandra; Carbo, Adria; Bruzzone, Santina; Tubau-Juni, Nuria; Philipson, Noah; Zoccoli-Rodriguez, Victoria; Sturla, Laura; Bassaganya-Riera, Josep (Frontiers in Nutrition, 2017)
Abscisic acid is naturally present in fruits and vegetables and it plays an important role in managing glucose homeostasis in humans. According to the latest U.S. dietary survey, about 92% of the population might have a deficient intake of ABA due to their deficient intake of fruits and vegetables. This review summarizes the in vitro, preclinical, mechanistic, and human translational findings obtained over the past 15 years in the study of the role of ABA in glycemic control. In 2007, dietary ABA was first reported to ameliorate glucose tolerance and obesity-related inflammation in mice. The most recent findings regarding the topic of ABA and its proposed receptor lanthionine synthetase C-like 2 (LANCL2) in glycemic control and their interplay with insulin and GLP-1 suggest a major role for ABA in the physiological response to a glucose load in humans. Moreover, emerging evidence suggests that the ABA response might be dysfunctional in diabetic subjects. Follow on intervention studies in healthy individuals show that low-dose dietary ABA administration exerts a beneficial effect on the glycemia and insulinemia profiles after oral glucose load. These recent findings showing benefits in humans, together with extensive efficacy data in mouse models of diabetes and inflammatory disease, suggest the need for reference ABA values and its possible exploitation of the glycemia-lowering effects of ABA for preventative purposes. Larger clinical studies on healthy, prediabetic and diabetic subjects are needed to determine whether addressing the widespread dietary ABA deficiency improves glucose control in humans.